The Assessment and Analysis of the Security Level of Countries - Davoyan, Samson; Asatryan, Vahe (Bulletin of Yerevan University G: Economics, 2025)
The security of the country is the mutually supported and balanced capabilities of its multi-institutional systems to resist internal and external threats, which can ensure the territorial integrity of the country, the stable and effective functioning of all its most important systems, economic, political etc.The purpose of the article is to study the individual components and directions of the country's security, to carry out a calculation and comparative analysis of the economic security of different countries using an integral index. Within the framework of the research, the foundation of the economic development of the country and the possibility of ensuring it at different levels of the country's security were also considered.
Keywords: Economy; safety; economic development; partial indexes; national security; global indexes